2014
DOI: 10.1021/la500101x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Mechanism of Coagulum Formation in Dispersions

Abstract: The stability of colloidal dispersions is of crucial importance because the properties of dispersions are strongly affected by the degree of coagulation. Whereas the coagulation kinetics for quiescent (i.e., nonstirred) and diluted systems is well-established, the behavior of concentrated dispersions subjected to shear is still not fully understood. We employ the discrete element method (DEM) for the simulation of coagulation of concentrated colloidal dispersions. Normal forces between interacting particles ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…16 We have already shown that in our simulations the exponent was equal to −0.65 ± 0.075, which is close to the scaling predicted by Equation 19.…”
Section: Scaling Of the Cluster Sizesupporting
confidence: 87%
See 1 more Smart Citation
“…16 We have already shown that in our simulations the exponent was equal to −0.65 ± 0.075, which is close to the scaling predicted by Equation 19.…”
Section: Scaling Of the Cluster Sizesupporting
confidence: 87%
“…19 This enables us to study the effect of the elasticity and adhesion of the primary particles on the properties of the clusters. The model is spatially three-dimensional and we implemented the two-way coupling between particles and flow to capture the hydrodynamic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The Johnson-Kendall-Roberts (JKR) [24] model for particle-particle adhesion/collision is employed. A number of works available in the literature have used this contact model for simulating aggregation/fragmentation process of particulate aerosol systems [16,17] and, more recently, cluster formation in shear-induced coagulation in a system made by hard spherical particles in water [25,26]. To the best of our knowledge, however, this is the first time that aggregation/breakage phenomena are studied for a system made by a water suspension of hard-gel particles flowing in a microfluidic device.…”
Section: Nomenclaturementioning
confidence: 99%
“…The production of many polymers often involves stages in which the monomer, polymer, or the intermediate products are dispersed into small particles. This adds a certain number of challenges that are mainly related to the colloidal stability of the latex . Unwanted particle coagulation is a major cost to the latex manufacturing industry mainly because of its negative effect on the product quality, product loss, and reactor down time.…”
Section: Cfd‐pbm Coupling Frameworkmentioning
confidence: 99%
“…This adds a certain number of challenges that are mainly related to the colloidal stability of the latex. [29] Unwanted particle coagulation is a major cost to the latex manufacturing industry mainly because of its negative effect on the product quality, product loss, and reactor down time. On the other hand, the ability to perform controlled coagulation in other circumstances is desirable, and it is important to be able to predict the impact of mixing and species concentrations in this particular case.…”
Section: Particle Coagulation Modelingmentioning
confidence: 99%